Impact of Preparative Isolation of C-Glycosylflavones Derived from Dianthus superbus on In Vitro Glucose Metabolism - Zikai Lin; Xiaowei Zhou; Chen Yuan; Yan Fang; Haozheng Zhou; Zhenhua Wang; Jun Dang; Gang Li (Molecules, 2024)
Dianthus superbus L. has been extensively studied for its potential medicinal properties in traditional Chinese medicine and is often consumed as a tea by traditional folk. It has the potential to be exploited in the treatment of inflammation, immunological disorders, and diabetic nephropathy. Based on previous studies, this study continued the separation of another subfraction of Dianthus superbus and established reversed-phase/reversed-phase and reversed-phase/hydrophilic (RPLC) two-dimensional (2D) high-performance liquid chromatography (HPLC) modes, quickly separating two C-glycosylflavones, among which 2″-O-rhamnosyllutonarin was a new compound and isomer with 6‴-O-rhamnosyllutonarin. This is the first study to investigate the effects of 2″-O-rhamnosyllutonarin and 6‴-O-rhamnosyllutonarin on cellular glucose metabolism in vitro. First, molecular docking was used to examine the effects of 2″-O-rhamnosyllutonarin and 6″-O-rhamnosyllutonarin on AKT and AMPK; these two compounds exhibited relatively high activity. Following this, based on the HepG2 cell model of insulin resistance, it was proved that both of the 2″-O-rhamnosyllutonarin and 6‴-O-rhamnosyllutonarin demonstrated substantial efficacy in ameliorating insulin resistance and were found to be non-toxic. Simultaneously, it is expected that the methods developed in this study will provide a basis for future studies concerning the separation and pharmacological effects of C-glycosyl flavonoids.